Analisis Komprehensif Penerapan Sistem Informasi Akuntansi dan Studi Kelayakan Finansial pada Rantai Pasok Agroindustri Ikan Tuna Beku Domestik - Ang Riqko Suhendi; Dudang Gojali; Nabiela Rizki Alifa (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to comprehensively analyze the implementation of Accounting Information Systems and financial viability in the domestic frozen tuna agro-industrial supply chain through a mixed-methods approach based on an empirical case study of tuna trading MSMEs at the Nizam Zachman Oceanic Fishing Port in Jakarta. The analysis was conducted using evaluations of operations, profitability, cash flow, capital structure, inventory turnover, and business strategy mapping through the SWOT analysis and Theory of Constraints. The results indicate that the implementation of the Accounting Information System improves inventory accuracy, accelerates financial statement reconciliation, and reduces levels of dead stock and distribution inefficiencies. The company also demonstrated stable profitability with a net profit margin above the industry average for commodity trading, supported by positive operating cash flow and a debt-free capital structure. Strategic analysis revealed that business expansion opportunities are significantly influenced by the ability to integrate the cold chain, diversify into value-added tuna products, and strengthen digital distribution. The research findings confirm that accounting digitization and supply chain optimization are the primary determinants of the sustainability and competitiveness of the modern domestic tuna agroindustry.